20 Development of an application for digital capture of informed consent in research. (22nd November 2019) - Kusi-Yeboah, Azariah; Ward, Dan; Murray, Ross; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil
Abstract : Introduction: Clinical trials and research studies are vital for treatment innovations. In order to give informed consent, participants are provided with information sheets that describe the study in detail. The current system is paper based and documents must be retained and archived. The aim of this project was to create a system to digitalise the process. Method: As part of a joint collaboration between GOSH and UCL computer science (CS) through the industry exchange network programme, we developed a mobile application for digital capture and management of consent. The application was based on a standard 3-tier (presentation, logic and data), software architecture pattern. The presentation tier consists of mobile and web applications. The mobile app was developed in Ionic4, while the web app makes use of Bootstrap to create fully responsive web pages. The logic tier, which contains the application's functional business logic, was written in Node.js and consists of the RESTful APIs the mobile and web app use to access data. The data tier comprises of a MySQL database. Results: A web application was developed to create study documentation that can be viewed and completed on a mobile app. The system allows for the management of study documents to ensure version control. User profiles for staff can be created to control access to studies, therefore only staff with permission can access documentation and consent participants to a research study. The application allows information sheets to be sent to by email to participants, and for signatures to be taken digitally. All completed paperwork can be stored on a cloud database. Conclusion: A proof of principle system for capturing consent electronically has been developed. This system could be further enhanced to provide a screen reader function and could incorporate animations or films to enhance the description of research studies to children.